A new mutation in the CAVIN1/PTRF gene in two siblings with congenital generalized lipodystrophy type 4: case reports and review of the literature - Mancioppi, Valentina; Daffara, Tommaso; Romanisio, Martina; Ceccarini, Giovanni; Pelosini, Caterina; Santini, Ferruccio; Bellone, Simonetta; Mellone, Simona; Baricich, Alessio; Rabbone, Ivana; Aimaretti, Gianluca; Akinci, Baris; et al. (Frontiers in Endocrinology, 2023)
Lipodystrophy syndromes are characterized by a progressive metabolic impairment secondary to adipose tissue dysfunction and may have a genetic background. Congenital generalized lipodystrophy type 4 (CGL4) is an extremely rare subtype, caused by mutations in the polymerase I and transcript release factor (PTRF) gene. It encodes for a cytoplasmatic protein called caveolae-associated protein 1 (Cavin-1), which, together with caveolin 1, is responsible for the biogenesis of caveolae, being a master regulator of adipose tissue expandability. Cavin-1 is expressed in several tissues, including muscles, thus, resulting, when dysfunctional, in a clinical phenotype characterized by the absence of adipose tissue and muscular dystrophy.We herein describe the clinical phenotypes of two siblings in their early childhood, with a phenotype characterized by a generalized reduction of subcutaneous fat, muscular hypertrophy, distinct facial features, myopathy and atlantoaxial instability. One of the siblings developed paroxysmal supraventricular tachycardia leading to cardiac arrest at three months of age. Height and BMI were normal. Blood tests showed elevated CK, a mild increase of liver enzymes and triglycerides levels, and undetectable leptin and adiponectin concentrations. Fasting glucose and HbA1c were normal, while HOMA-IR was mildly elevated. Both patients were hyperphagic and had cravings for foods rich in fats and sugars. Genetic testing revealed a novel pathogenic mutation of the CAVIN1/PTRF gene (NM_012232 exon1:c T21A:p.Y7X) at the homozygous state.The diagnosis of lipodystrophy can be challenging, often requiring a multidisciplinary approach, given the pleiotropic effect, involving several tissues. The coexistence of generalized lack of fat, myopathy with elevated CK levels, arrhythmias, gastrointestinal dysmotility, and skeletal abnormalities should prompt the suspicion for the diagnosis of CGL4, although phenotypic variability may occur.